2014
DOI: 10.3171/2014.6.jns131321
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of a concurrent series of microscopic versus endoscopic transsphenoidal surgeries for Knosp Grades 0–2 nonfunctioning pituitary macroadenomas at a single institution

Abstract: N eurosurgeoNs have traditionally used a sublabial or transseptal incision with an operating microscope to access the sphenoid sinus and sella turcica for the resection of pituitary tumors. 9 Over the past decade, however, the endoscopic endonasal transsphenoidal approach has become an increasingly popular method of removing pituitary tumors and other lesions of the sella. 2,3,7,12,20 Among the arguments proposed for the use of endoscopy for transsphenoidal surgery are that it provides a superior view of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 22 publications
2
46
0
Order By: Relevance
“…The adoption of the fully endoscopic technique has occurred because of the belief that the improved visualization it offers leads to better gland preservation rates and better EOR; however, there are limited studies with high-quality objective outcomes data comparing fully endoscopic surgery to microscopebased techniques to justify this trend. As more centers have gained experience with fully endoscopic techniques, several meta-analyses and single-center experiences have been published 1,6,7,10,14,16,21,23 (Table 7). The primary limitations of previous series that we have tried to address in this study are the absence of formal volumetric EOR data, experimental cohorts containing several tumor types, lack of rigorous endocrine outcomes reporting, and the fact that most published comparisons of techniques represent cases performed by a single surgeon in different surgical epochs rather than concurrently performed cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The adoption of the fully endoscopic technique has occurred because of the belief that the improved visualization it offers leads to better gland preservation rates and better EOR; however, there are limited studies with high-quality objective outcomes data comparing fully endoscopic surgery to microscopebased techniques to justify this trend. As more centers have gained experience with fully endoscopic techniques, several meta-analyses and single-center experiences have been published 1,6,7,10,14,16,21,23 (Table 7). The primary limitations of previous series that we have tried to address in this study are the absence of formal volumetric EOR data, experimental cohorts containing several tumor types, lack of rigorous endocrine outcomes reporting, and the fact that most published comparisons of techniques represent cases performed by a single surgeon in different surgical epochs rather than concurrently performed cases.…”
Section: Discussionmentioning
confidence: 99%
“…This is the most commonly reported method in pituitary series. 6,16,21 Patients with questionable residual tumor on postoperative imaging were assigned to the STR outcome. Second, formal volumetric analysis using manual tumor tracing was performed using manual segmentation with region of interest analysis to measure tumor volume (in cm 3 ) on the basis of contrast enhancement, as previously described.…”
Section: Extent Of Resection Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…This form of selection bias takes into account individual training and experience, along with issues about the individual tumor, yet does not necessarily detract from the validity of observation. 6 The nature of this form of selection bias is becoming more recognized in surgical studies, and in fact it has been suggested that this bias is built into the design of RCTs.…”
Section: Potential Limitationsmentioning
confidence: 99%